An Exploration of Factors Contributing to the Perceptions of Preparedness for Elementary Candidates in a Clinically Based Program. (9th January 2014) - Giles, Rebecca McMahon; Kent, Andrea M.
Abstract : A quantitative, descriptive research model was used to investigate the perceptions of teacher candidates ( n = 32 ) in a clinically based dual certification program regarding their culminating student teaching experience. Data consisted of candidates' responses to both multiple choice and open ended survey items. Results indicated that teacher candidates within an undergraduate program leading to state teaching certification in both elementary and collaborative teaching (K-6) had positive perceptions regarding their preparedness as a result of prior experiences working in K-6 classrooms (44%) and interactions with in-service teachers (28%). In addition, teacher candidates perceived strong relationships with their university supervisors reporting that they received a greater amount of encouragement and feedback for improved teaching from their university supervisors than from their cooperating teachers.